Surveillance of Employee Cooperation in the Enactment of Services in the Paguyaman Pantai Sub-District Office - Pepi Rahman; Sudarsono; Samin Latif (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to discover how the employee of Paguyaman Pantai sub-district office manages the cooperation in providing services. This study employed a descriptive method with a qualitative approach. The data analysis technique utilizes the Miles and Huberman model to process the data. The findings indicated that 1) Employees' competency in implementing services exhibits unique features. There are still some employees that violate time discipline regulations and even disregard their assigned jobs and responsibilities. 2) It is assumed that the employees' synergy in delivering services has been established well and smoothly and that any issues would be resolved by mutual discourse. 3) Relationships with employees involved in service delivery are positive and smooth, as they consistently develop communication and coordination regarding performance as sub-district employees. 4) Employee productivity in implementing services has been extremely high, as evidenced by the excellent cooperation built as quickly as feasible. 5) Employees' sense of belonging is still a barrier to service delivery at the Paguyaman Pantai Sub-District Office due to a lack of trust between employees and individual attitudes.